A Theory of Claim Resolution. (10th December 2021) - Baker, Scott; Kornhauser, Lewis A
Abstract: We study claim resolution. A claim consists of a global fact and a local fact. The global fact is observed by the principal and the agent. The local fact is observed by the agent alone. The agent resolves the claim; the principal decides whether the agent is more likely wrong or right. The principal and agent can disagree about the weight to accord each fact or the overall evidence threshold. The agent cares whether the principal follows or ignores her advice. We characterize how the equilibrium varies with the nature of disagreement. Despite lacking commitment power, we find that the principal grants the agent decision-making authority over an interval of global facts. Further, we find that the principal can better motivate an agent who excessively weights the local fact than an agent who excessively weights the global fact. The principal strictly prefers the former to the latter even though either would make the same number of errors if granted complete autonomy. (JEL C7, K0, D7, K4, M4)